Juridical Review of The Issuance of Ministerial Regulations Without Any Delegation From The Law (Case Study of the Regulation of the Minister of Home Affairs Number 4 of 2023 on Acting Governor, Acting Regent, and Acting Mayor) - Raissa Safatiara; Citraresmi Widoretno Putri (Journal of Law, Politic and Humanities, 2024)
Ahead of the syncronous Pilkada that to be run in November 2024, there is still a polemic related to the legal guidelines for the acting of regional heads’s levitation whose term of office ends ahead of the 2024 simultaneous elections. The legal basis for the Minister of Home Affairs Regulation Number 4 of 2023 concerning Acting Regional Heads issued by the Minister of Home Affairs is considered to have many irregularities. This paper will reveal the absence of statutory delegation in the issuance of the Permendagri and the use of legal considerations of the Constitutional Court judges in the Constitutional Court Decision Number 15/PUU-XX/2022 as a consideration in the Permendagri. The research method used in this paper is normative juridical through a statutory approach as a source of existing law. The results of this study conclude that the issuance of Permendagri No. 4 of 2023 is unfounded if only viewed through the presence or absence of delegation of the formation of implementing regulations. If viewed more broadly through the theory of discretion, then this is considered valid, in order to fill the legal vacuum. The legal deliberations of the Constitutional Court judges in MK’s Decision Number 15/PUU-XX/2022 also strengthen the legitimacy of the issuance of Permendagri No. 4 of 2023, this is because the content of the legal considerations is considered to be commensurate with the ruling, even though the ruling was rejected.  Unfortunately, the implementing regulation chosen by the government to regulate the inauguration of acting regional heads is in the form of a Minister of Home Affairs Regulation, not a Government Regulation.